Assessment of the Contribution of Female Head Teachers to Academic Performance in Junior High Schools in Northern Ghana - Alhassan, Eliasu; Duorinaah, Eric (EBSU Journal of Social Sciences and Humanities, 2021)
The study assesses the contribution of female head teachers to pupils’ preparation and their eventual performance in Basic Education Certificate Examination in selected Junior High Schools in Northern Ghana. Through cross sectional design, the study comprised 351 respondents from district, community and selected Junior High Schools in Northern Ghana. Data collected from questionnaire and interviews were analysed along common themes and strengthened by descriptive statistics. The study reveals that there are many factors accounting for few female heads in the basic schools in the Northern Region of Ghana. Among these includes the availability of females teachers who are qualified to take up headship positions, unwillingness by many available females to accept headship and in some instances discrimination against female teachers when it comes to headship positions because many of those doing the appointment are males. The study further showed that headship at the Junior High School level is male dominated and only 16.8% of head teachers were females. Characterized by varied perceptions and preferences for some leaders pupils under the few female heads demonstrated a more improved scores in their Basic Certificate Examinations compared with those under males headships. It is recommended that more females be recruited as head teachers and supported with in-service training in the areas of planning, budgeting and relationship building. Also female teachers should be targeted and supported to attend short courses on leadership all in a bid to motivate them to take up headship. Ministry of Education also needs to institute a policy which mandates that where female teachers have the minimum requirement they should automatically be made the assistant head teacher so that as soon as the headship becomes vacant they can be considered.